2022
DOI: 10.1021/acsomega.2c04425
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Cu Nanoparticles Dispersed on ZnAl-Layered Double Hydroxide Nanocatalysts for the Oxidation of Cyclohexane

Abstract: In the chemical industry, designing high-performance catalysts for the oxidation of cyclohexane into value-added products such as cyclohexanol and cyclohexanone (the combination is known as KA oil) is critical. The catalytic activity of copper nanoparticles supported on layered double hydroxide (LDH) for the liquid phase oxidation of cyclohexane was examined in this study. In this work, we have developed Cu nanoparticles supported on layered double hydroxide nanocatalysts, abbreviated as CuNPs@LDH, by the chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…56 Xu et al reported cyclohexane oxidation with honeycomb-like nanostructures with a N doping-supported bimetallic Ce−Cr oxide catalyst, and they have achieved 56.5% conversion with 95.5% selectivity to KA oil. 57 Wu et al conducted cyclohexane oxidation over bimetallic Au−Pt and Au−Pd supported on mesoporous silica, and they achieved cyclohexane conversion of 6% with 99% selectivity to KA oil. 58 Overall results suggest that the conversion of cyclohexane (62%) and KA oil selectivity (95%) achieved in the present study were higher than those of recent literature reports.…”
Section: Reaction Study Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…56 Xu et al reported cyclohexane oxidation with honeycomb-like nanostructures with a N doping-supported bimetallic Ce−Cr oxide catalyst, and they have achieved 56.5% conversion with 95.5% selectivity to KA oil. 57 Wu et al conducted cyclohexane oxidation over bimetallic Au−Pt and Au−Pd supported on mesoporous silica, and they achieved cyclohexane conversion of 6% with 99% selectivity to KA oil. 58 Overall results suggest that the conversion of cyclohexane (62%) and KA oil selectivity (95%) achieved in the present study were higher than those of recent literature reports.…”
Section: Reaction Study Resultsmentioning
confidence: 99%
“…The cyclohexane oxidation reaction was performed by Han et al using graphene-supported CoO nanoparticles, and the process achieved 32% conversion and 75% KA oil selectivity . Xu et al reported cyclohexane oxidation with honeycomb-like nanostructures with a N doping-supported bimetallic Ce–Cr oxide catalyst, and they have achieved 56.5% conversion with 95.5% selectivity to KA oil . Wu et al conducted cyclohexane oxidation over bimetallic Au–Pt and Au–Pd supported on mesoporous silica, and they achieved cyclohexane conversion of 6% with 99% selectivity to KA oil .…”
Section: Resultsmentioning
confidence: 99%
“…LDHs can be used as an attractive base in various applications, such as medical, pharmaceutical, sensors, and drug delivery. As a result, they have attracted a lot of attention. LDHs have a layered structure, which is also called hydrotalcite; it consists of divalent and trivalent cations, whose general formula is [Me 2+ (1 – x ) Me 3+ x (OH) 2 ] x +(An – ) x / n n •H 2 O. , It is possible to change cations and anions, which may affect the properties of the layers. Today, layered double hydroxides are excellent supports for various catalysts due to the numerous hydroxide groups on their surface. …”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, we reported that Cu and CeO 2 nanoparticles and Co Schiff base complexes were synthesized and immobilized on layered double hydroxide catalysts. Their catalytic activity has been investigated for the oxidation of cyclohexane and ethylbenzene [19][20][21].…”
Section: Introductionmentioning
confidence: 99%